2023
DOI: 10.1021/acs.jpcc.2c08044
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cluster Sources on the Growth Mechanisms and Chemical Composition of Bimetallic Nanoparticles

Abstract: Metal nanoparticles are omnipresent in today’s applied and fundamental research. Both wet-chemical as well as physical procedures for their fabrication are well-established, where the latter is of particular interest as they supply surfactant-free particles. Particle growth has been investigated for several decades, but due to its complexity, involving kinetic and dynamic processes on various length and time scales, often only phenomenological rules of thumb are available. In this study, we report on bimetalli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 73 publications
1
9
0
Order By: Relevance
“…The HSI used for the present study (Figure ) contains 19 particles and the corresponding relative chemical composition as a function of size is shown in Figure S3, with a mean composition of C Ag = 0.513 ± 0.003. Note that the fact that the smallest BNP displays a significantly higher proportion of Ag is consistent with our previous work and can be attributed to the BNP formation in the source. In this study, however, we will not address this point in detail, and we will focus on the distribution of chemical elements inside individual BNPs.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The HSI used for the present study (Figure ) contains 19 particles and the corresponding relative chemical composition as a function of size is shown in Figure S3, with a mean composition of C Ag = 0.513 ± 0.003. Note that the fact that the smallest BNP displays a significantly higher proportion of Ag is consistent with our previous work and can be attributed to the BNP formation in the source. In this study, however, we will not address this point in detail, and we will focus on the distribution of chemical elements inside individual BNPs.…”
Section: Resultssupporting
confidence: 91%
“…Figure 1b shows EDS data and Figure 1c displays typical highangle annular dark-field STEM (HAADF-STEM) results from bimetallic NPs generated in a gas-aggregation source (a typical size distribution can be found in previous work on this system 34 ). The atomic structure of AuAg NPs obtained under the very same conditions were already described elsewhere 35 and here, we will focus only on their chemical composition gradient studied by STEM EDS.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, silver surface segregation was consistently found in simulations when using empirical force fields. 70,71,73,74,102 However, in this context, the simplicity of the employed empirical force fields when compared to our MLIP may lead to inaccurate modeling. In particular, in the work of Paz-Borbón et al, 73 the Gupta potential seemed at first to demonstrate silver segregation but when further optimization was made at the DFT level, the authors found that gold segregation was favored instead.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, in the work of Paz-Borbón et al, 73 the Gupta potential seemed at first to demonstrate silver segregation but when further optimization was made at the DFT level, the authors found that gold segregation was favored instead. Similarly, we tested an embedded-atom model (EAM) which was used in the recent paper of Moreira et al 102 and demonstrated that it leads to much more energetic nanoparticles when exhibiting silver surface segregation [see ESI J †].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the morphology and topology of bimetallic NPs, intense computational efforts have been devoted to understanding the chemical ordering and the structural evolution by using DFT calculations and Monte Carlo simulations. 19,20,22,25–27 These efforts received several experimental confirmations, indicating the good accuracy of the theoretical results. 19,20,22,25–27 Clearly, not all real-world features can be considered, such as the presence and types of solvents in colloidal synthesis or the oxidation path promoted by the environment.…”
Section: Introductionmentioning
confidence: 90%